A continuous simulation approach to quantify the climate condition effect on the hydrologic performance of green roofs. Issue 7 (8th August 2020) - Palla, Anna; Gnecco, Ilaria
ABSTRACT: In order to effectively estimate the hydrologic performance of green roofs, continuous simulation approaches are recently used thus allowing to include the precipitation regime features as well as the varying soil moisture conditions. Continuous simulations are implemented in the EPA Storm Water Management Model (SWMM) using as input data the climate data series recorded at three Italian sites (Bergamo, Genoa and Castelbuono) while a simple methodological approach is adopted to estimate the actual evapotranspiration. Results are examined at the event scale by means of the volume and the peak reduction rates. Results confirm the positive impact of green roof retrofitting scenario for all the investigated climate regimes. On the other hand, the specific rainfall characteristics at the event scale (mainly rainfall depth and antecedent dry weather period) affect both the retention and detention performance of green roofs.